Producing European modernity mythmaking and (racial) bourgeois-capitalist worldmaking in modern philosophical and literary writings - Cvijanović, Hrvoje (2020)
This paper examines the ways in which modern philosophical and literary accounts have shaped and produced European modernity. The author looks at the myth as such, but especially in the quest, justifications, and narratives provided by Rousseau, Locke, and Daniel Defoe, among all. They are seen as grounding examples of modern mythmaking in which the concept of savagery has been uplifted and opposed to cultivating and civilizational practices, and used as a conceptual axis for articulating ideas of progress, self-preservation, and the state of nature. It is shown that modern bourgeois power of mythmaking through writing cannot be detached from racial bourgeois-capitalist worldmaking, or from the production and reproduction of racial capitalism – a structural and historical nexus of capitalism and racial oppression. The article concludes that by perpetuating myths of rational individuals rationally organizing the world, cultivating the wilderness, and enjoying freedom of production and consumption, European bourgeoisie conceptualized and constructed a fictional framework of modern man set within the mechanism of the modern state and capitalist production, that legitimized the predatory socio-economic practices based on harvesting social and natural resources, the same practices held by global capitalism as well.
Bibliografske bilješke uz tekst ; bibliografija: str. 103-105.
Summary.
Keywords: Modernizam -- Mitovi -- Filozofsko gledište -- Književnost -- Rasni kapitalizam